Prioritas Persepsi Permodalan Dan Strategi Prioritas Sumber Modal Usahatani Padi Sawah : Analisis AHP Dan SWOT - Imelda Zakir; Yuliana Bakari; Asda Rauf; Mohammad Zubair Hippy (JSEP (Journal of Social and Agricultural Economics), 2023)
One of the most important factors of production in the agricultural sector is capital. This research aims to analyze perception of capital and efficiency strategy of capital sources for lowland rice farming in Suwawa Subdistrict, Bone Bolango Regency. The research sample size is determined using Harry King’s Nomogram. This current research uses a quantitative descriptive approach and primary and secondary data. Primary data are collected througt techniques of observation, interview, and documentation with respondents. Data analysis in this research employs Analytical Hierarchy Process (AHP) analysis and SWOT analysis. The research finding on perception of lowland rice farming capital indicates that farmers tend to choose their own capital rather than loan capital in farming financing. Furthermore, the efficiency strategy for farming capital sources based on SWOT analysis is in quadrant one with the strength-opportunities (SO) strategy.